Harnessing the Potential of Insectivorous Birds in Managing the Rice Leaf Folder, Cnaphalocrocis Medinalis in Paddy Ecosystems of Kerala - Ranjith M T; Mani Chellappan; Vipin Chaudhary (International Journal of Insects, 2024)
This study evaluates the effectiveness of various treatments for managing leaf folder pests in rice crops during the maximum tillering stage, focusing on the role of insectivorous birds. The treatments included bird perches (T1), nylon nets (T2), Bt spray (T3), a combination of bird perch and Bt spray (T4), flubendiamide spray (T5), and a control group (T6). Results indicated significant differences in pest densities. T2 showed the highest mean density at 5.28 (27.50), reflecting their protective effect against bird predation. In contrast, the T6 had a density of 4.58 (20.56), while T1 reduced pest density to 3.52 (12.12). The T3 resulted in a mean density of 3.10 (9.37), and the combination treatment produced a density of 2.95 (8.50), showing no additive effect between the two methods. T5 was the most effective treatment, achieving a density of 1.74 (3.25), though it raised sustainability concerns. Overall, the findings advocate for a holistic pest management approach that integrates ecological strategies, such as promoting insectivorous birds, with chemical methods to enhance sustainability in rice cultivation. This integrated strategy can improve pest control while minimizing environmental impacts, contributing to more sustainable agricultural practices and better crop yields. By considering both ecological and chemical interventions, farmers can achieve effective pest management while protecting biodiversity.
Keywords: Granivorous birds; bio-bird repellent; nylon net; reflective ribbon; rice; rope grid